2018
DOI: 10.1093/jac/dky164
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of an XDR and carbapenemase-producing hypervirulent Klebsiella pneumoniae strain in Taiwan

Abstract: We identified an XDR ST11 KPC-2-producing K. pneumoniae strain carrying a hybrid virulent plasmid in Taiwan. Active surveillance focusing on carbapenem-resistant hypervirulent K. pneumoniae strains is necessary, as the threat to human health is imminent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 31 publications
6
101
1
2
Order By: Relevance
“…Moreover, Liu et al found that hvKp strains with antimicrobial resistance causing VAP are increasing [25], consistent with the fact that MDR-hvKp strains have emerged in China and are usually fatal due to the limited choice of antimicrobials and their virulence [26,27]. We have recently reported the high mortality associated with MDR-hvKp infections in Taiwan [28,29], and we identified 14 MDR-hvKp strains in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, Liu et al found that hvKp strains with antimicrobial resistance causing VAP are increasing [25], consistent with the fact that MDR-hvKp strains have emerged in China and are usually fatal due to the limited choice of antimicrobials and their virulence [26,27]. We have recently reported the high mortality associated with MDR-hvKp infections in Taiwan [28,29], and we identified 14 MDR-hvKp strains in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…To date the majority of hypervirulent K. pneumoniae have remained susceptible to antimicrobials [38,46] (except ampicillin). However, the last few years have seen increasing reports of "convergent" K. pneumoniae that are both hypervirulent (defined as strains carrying the iuc aerobactin locus) and MDR ESBL/CP either due to acquisition of an MDR plasmid by a hypervirulent strain [47][48][49][50][51] or by acquisition of a virulence plasmid by an MDR strain [49,[52][53][54][55][56]. The majority of these reports represent sporadic isolations.…”
Section: Introductionmentioning
confidence: 99%
“…This issue occurs not only in pathogenic bacteria but also in non-pathogenic bacteria. The emergence of multidrug-resistant bacteria (MDR) has increased in the last decade and has caused public concerns around the world (Huang et al, 2018). Many studies have been reported that in Brazil, about 71.0% of the E. coli isolates from commercial chicken carcasses were MDR (Magiorakos et al, 2012); in Italy, 66.9% of the E. coli isolates from chicken meat were MDR (Ghodousi et al, 2015); in Egypt, 100% of the E. coli isolates from avian source were MDR (Enany et al, 2019), which demonstrated the high antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%